Determination of conversion coefficients from the decay of PB202m by means of a semiconductor detector - Bosch, Horacio; Krmpotic, F.; Plastino, A. (North Holland Publishing, 1964)
Fil: Bosch, Horacio Comisión Nacional de Energía Atómica; Argentina